Salivary enzymes in peptic ulcer disease - Mojdeh Motamedi; Fariborz Mansour-Ghanaei; Reyhaneh Sariri; Mahmoud Vesal (Elsevier, 2013)
Aim: Peptic ulcer, the common disease of the upper gastro-intestinal tract, occurs in about 5-10% of the world's population. Therefore, diagnosis of trace disease progression with a noninvasive method is of prime importance in the field of healthcare research. The aim of this study was to evaluate the validity of salivary enzymes as noninvasive biomarkers for peptic ulcer. Materials and methods: In practice, 34 peptic ulcer patients and 30 healthy subjects donated their un-stimulated saliva samples after 8 h of fasting. The activity of some selected enzymes was measured using appropriate enzymatic assay methods. Results: The results indicated an overall alternation in enzymatic activity of saliva in patients suffering from peptic ulcer. Biological activity of a-amylase, peroxidase and lactate dehydrogenase, showed significantly higher values in almost all patients as compared to control subjects. Conclusions: Based on the results of salivary enzyme activity, it was concluded that besides the influence of their peptic ulcer on enzyme activity of saliva, the considerably higher activity of a-amylase could also be related to the major role of the enzyme on physiological oxidative stress.